Democracy, emergency, and arbitrary coercion : a liberal Republican view - Sagos, Nick C. (Studies in Moral Philosophy, 2014)
States of emergency are declared by governments with alarming frequency. When they are declared, it is taken for granted that their nature is understood. This book argues against this established view. Instead, the view advanced here analyzes what makes emergencies different from other types of similar events. Defending a hybrid liberal/republican approach, the book proposes that states of emergency are in fact poorly understood and therefore needlessly mismanaged when they occur. This mismanagement leads to a troubling derogation of established liberal democratic rights in the name of an unattainable form of hollow security. Further, the book argues that the existing rights of citizens ought to be defended (and not simply derogated) during states of emergency. Failure to do so is failure to comply with the formal values of liberal democracy itself.